Experimental Research on Heating Performance of Rotary Compression System with Vapor Injection - Jia Qinglei; Feng Liwei; Yan Gang (Zhileng xuebao, 2015)
In this paper, the single-cylinder rotary compression system with vapor injection is applied in heat pump system to solve the problems of insufficient heating capacity and lower efficiency during lower ambient conditions. The system performances of single-cylinder rotary compression system with vapor injection (called single-cylinder system), dual-cylinder rotary compression system with vapor injection (called dual-cylinder system) and single stage compression system were comparatively tested under the different heating conditions in psychrometric room. The results show that the single-cylinder system has a higher heating capacity compared with single stage compression system when the outdoor temperature is above ﹣15 ℃, and the rates of increase is above 12%. The rate of increase is increased along with the decrease of ambient air temperature. The heating capacity and COP of single-cylinder system are higher than that of the dual-cylinder system, and the increasing ranges are 2.29%, 1.94% respectively. When the outdoor temperature is below ﹣15 ℃, single stage compression system would not operate normally due to the higher discharge temperature. The heating capacity and COP of dual-cylinder system are higher than that of the single-cylinder system, and the increasing ranges are 4.5%, 9.42% respectively. Therefore, the single-cylinder system is suitable for the conditions of outdoor temperature above﹣15 ℃, while the dual-cylinder system is suitable for the conditions of outdoor temperature below ﹣15 ℃.